Sistema automático de controlo de transferência de líquidos - Vieira, Daniel Xavier Silva (2022)
The project described in this document arises from the need to automate racking systems that the Watgrid company has found in the wine industry, and in its production process. The document describes the implementation of the control system composed by electrovalves, transfer pumps and liquid level sensors, through a PLC which communicates through WiFi. The project consists in the development of a mock-up representing a structure with four containers connected by tubes, with the proper actuation units properly installed. To this end, a survey of functional prerequisites and existing commercial solutions for the various components was carried out. After the conceptual development of the physical structure of the mock-up, the solutions found for the modules that simulate the operation of the actuating units were implemented, up to the structure that integrates these modules. A PLC software unit was also developed to control in the various stages of the system's implementation. It is also mentioned the implementation of an user interface allocated on a web server created in the PLC WiFi module. The purpose of the mock-up lies in the assumption of replicating a direct application in a real system. Thus, it was possible to progressively implement a control algorithm for the PLC that reproduces the intended process and perform functional tests on the system. Finally, test results were recorded and analysed for the normal operation of the system and in situations of unforeseen failures that could compromise the integrity of the racking process.